Peningkatan Keterampilan Berbicara melalui Pendekatan Communication Language Teaching (CLT) dan Strategi NHT pada Pembelajaran Bahasa Indonesia Kelas V SDN Ngabeyan 3 tahun 2016/2017 - Lestari, Fitri; , Dra. Sri Hartini, SH., M.Pd (2017)
The language component must be mastered by students is to talk. Speaking skills must be mastered by every student because these skills will affect the whole process of learning activities of students at the school. Efforts to improve the speaking skills is to use the approach of Communication Language Teaching (CLT) and strategy of NHT. The purpose of this study: (1) improving speaking skills of students in the Indonesian Language learning approach to Communication Language Teaching (CLT) and strategy of NHT on class V SDN Ngabeyan 3 lesson years 2016/2017, (2) improving activity of the teachers in the implementation of the approach of Communication Language Teaching (CLT) and strategy in learning Indonesian Language grade NHT class V SDN Ngabeyan 3 lesson years 2016/2017. This type of research this is a class action research (PTK). This research model using the model of Kurt Lewin. Engineering data collection using the observation activities of teachers and students, learning Indonesian Language execution, interview and documentation. The results of this study are: (1) Learning speaking skills by using the approach of Communication Language Teaching (CLT) and strategies Numbered Heads Together (NHT) carried out on a regular basis can improve your speaking skills grade V SD Negeri Ngabeyan 3 lesson years 2016/2017. (2) Teachers to apply the approach of Communication Language Teaching (CLT) and strategies Numbered Heads Together (NHT) thoroughly in accordance with steps of learning.